Mapping out Methodological Approaches to Russian Symbolism (on the Example of Vyacheslav Ivanov) - Svetlana V. Fedotova (Studia Litterarum)
This article is a multidimensional study of Russian symbolism as one of the most prominent 20th century literary schools that had a major impact on the development of Russian modernism. The current state of art in the field of modernism is relevant in the context of the metamodern paradigm. The article specifically focuses on the figure of Vyacheslav Ivanov, symbolist poet, leading theoretician of this literary school, and religious thinker who played important role in the development of the so-called Silver Age in Russian literary history. The purpose of the article is to map out methodological approaches, representative of contemporary studies of Vyach. Ivanov. The study bears on the corpus of the most interesting works on Ivanov in the past decades. It demonstrates that besides traditional philological readings, there are a number of novel approaches to the poet’s heritage based on philosophical, linguophilosophical, cultural, religious-axiological, psychoanalytic, hermeneutic, intertextual, or comparative perspective.